Working Memory in the Classroom: An Inside Look at the Central Executive. Issue 3 (2nd July 2016) - Barker, Lauren A.
Abstract : This article provides a review of working memory and its application to educational settings. A discussion of the varying definitions of working memory is presented. Special attention is given to the various multidisciplinary professionals who work with students with working memory deficits, and their unique understanding of the construct. Definitions and theories of working memory are briefly summarized and provide the foundation for understanding practical applications of working memory to assessment and intervention. Although definitions and models of working memory abound, there is limited consensus regarding universally accepted definitions and models. Current research indicates that developing new models of working memory may be an appropriate paradigm shift at this time. The integration of individual practitioner's knowledge regarding academic achievement, working memory and processing speed could provide a foundation for the future development of new working memory models. Future directions for research should aim to explain how tasks and behaviors are supported by the substrates of the cortico-striatal and the cerebro-cerebellar systems. Translation of neurobiological information into educational contexts will be helpful to inform all practitioners' knowledge of working memory constructs. It will also allow for universally accepted definitions and models of working memory to arise and facilitate more effective collaboration between disciplines working in educational setting.